2009
DOI: 10.1111/j.1600-0765.2008.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Early osteogenic differential protein profile detected by proteomic analysis in human periodontal ligament cells

Abstract: Our results suggest that the proteins identified in this study may be associated with the unique function of periodontal ligament cells in maintaining periodontal tissue homeostasis, thus providing a comprehensive reference for understanding and investigating in greater detail the molecular mechanisms of periodontal ligament cells involved in periodontal regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
(55 reference statements)
1
30
0
1
Order By: Relevance
“…TBCA is a tubulin folding cofactor, which is essential for cell cytoskeleton function [38]. The up-regulated TBCA in PDLCs may be associated with the unique function of PDLCs in the maintenance of the periodontium as well [39].…”
Section: Discussionmentioning
confidence: 99%
“…TBCA is a tubulin folding cofactor, which is essential for cell cytoskeleton function [38]. The up-regulated TBCA in PDLCs may be associated with the unique function of PDLCs in the maintenance of the periodontium as well [39].…”
Section: Discussionmentioning
confidence: 99%
“…During early cementoblastic/osteogenic differentiation of periodontal ligament stem cells, a total of 29 differentially expressed proteins were identifi ed by DIGE (Wu et al 2009 ) . Reduced expression of cytoskeletal proteins vimentin, caldesmon and tropomyosin is thought to relate to cytoskeletal rearrangements during differentiation processes while the regulation of binding partners caldesmon and tropomyosin also plays a role in cytokenesis as discussed earlier in the chapter.…”
Section: Periodontal Ligament Stem Cellsmentioning
confidence: 99%
“…In our previous studies (3,5,6), we have shown that DPCs and PDLCs are similar with respect to morphology and expression of cell surface markers (Stro-1, CD146, CD29-Fluorescein isothiocyanate (FITC), CD34-FITC, CD44-FITC, and CD106-FITC) and that both possess odontogenic/osteogenic differentiation potential. Recently, we investigated the differential protein expression profile of human DPCs and PDLCs undergoing odontogenic/osteogenic differentiation by using Two dimensional difference gel electrophoresis and mass spectroscopy based proteomic approaches (5,6).…”
mentioning
confidence: 99%
“…Recently, we investigated the differential protein expression profile of human DPCs and PDLCs undergoing odontogenic/osteogenic differentiation by using Two dimensional difference gel electrophoresis and mass spectroscopy based proteomic approaches (5,6). In odontoblast-like differentiation of DPCs, proteins involved in cell cycle regulation, protein synthesis and degradation, Ca 2+ homeostasis, signal transduction, translation, and cellular energy regulation have been shown to be differentially expressed (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation